2020
DOI: 10.1007/s10615-020-00779-4
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Clinical Training Simulations with Virtual Clients Abusing Alcohol: Initial Feasibility, Acceptability, and Effectiveness

Abstract: Although masters-level social work students typically build clinical skills via role-playing with their peers or instructors, several innovative training simulations are emerging in the literature that may enhance existing skill-building methodologies. We evaluated the initial feasibility, acceptability, usability, and effectiveness of three computerized simulations (two cognitive behavioral therapy, one motivational interviewing) during an interpersonal practice course among 22 students in a Master of Social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In pilot work, 22 social work students were given access to two cognitive behavioral and one motivational interviewing computer simulation program as part of an enhanced practice course. Usability and acceptability outcomes showed sustained program engagement, self-reported acceptability, and changes in simulation scores in a within-group, pre-post design (Smith et al, 2020 ). Another pilot study of practicing healthcare providers ( N = 20) showed similar acceptability, engagement, and changes in knowledge scores for suicide assessment (O’Brien et al, 2019a , b ).…”
Section: Resultsmentioning
confidence: 99%
“…In pilot work, 22 social work students were given access to two cognitive behavioral and one motivational interviewing computer simulation program as part of an enhanced practice course. Usability and acceptability outcomes showed sustained program engagement, self-reported acceptability, and changes in simulation scores in a within-group, pre-post design (Smith et al, 2020 ). Another pilot study of practicing healthcare providers ( N = 20) showed similar acceptability, engagement, and changes in knowledge scores for suicide assessment (O’Brien et al, 2019a , b ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found that tobacco treatment training increases knowledge, competency, and self-efficacy in tobacco treatment delivery by MHPs ( 30 ). Moreover, a more recent study assessing the use of virtual simulation to enhance counseling skills for alcohol dependence treatment among social work master's level students found that engagement in the simulation-based training resulted in improved self-efficacy and general clinical skills ( 31 ). In a similar fashion, our study findings provide some level of validation for the use of animated scenarios to enhance knowledge acquisition and intentions to change practice.…”
Section: Discussionmentioning
confidence: 99%
“…SIMmersion uses a proprietary technology called PeopleSim to increase knowledge acquisition, allow for skill-building practice, and provide integrated feedback required to develop advanced skills in their computer-assisted clinical training sessions with virtual human clients. Prior studies of SIMmersion's non-suicide-focused simulations have demonstrated that trainees effectively learned to use clinical techniques such as client engagement, mental and behavioral health screening, CBT, and MI (Huttar & BrintzenhofeSzoc, 2020; Mastroleo et al, 2020; Putney et al, 2021; Smith et al, 2021; Washburn et al, 2020).…”
Section: Methodsmentioning
confidence: 99%